1992
DOI: 10.1007/bf00317239
|View full text |Cite
|
Sign up to set email alerts
|

Light and dark CO2 fixation in Clusia uvitana and the effects of plant water status and CO2 availability

Abstract: In well-watered plants of Clusia uvitana, a species capable of carbon fixation by crassulacean acid metabolism (CAM), recently expanded leaves gained 5 to 13-fold more carbon during 12 h light than during 12 h dark periods. When water was withheld from the plants, daytime net CO uptake strongly decreased over a period of several days, whereas there was a marked increase in nocturnal carbon gain. Photosynthetic rates in the chloroplasts were hardly affected by the water stress treatment, as demonstrated by meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 18 publications
1
46
0
Order By: Relevance
“…This could represent futile cycling through malate production and decarboxylation , but a recent study on C. minor suggests that futile cycling is negligible during phase I1 in both control and N,-treated plants, although it may occur during phase IV (Borland and Griffiths, 1997; see also Osmond et al, 1996). In ,terms of overall carbon balance, regardless of the magnitude of phase I dark CO, uptake imposed by the various treatments, leaves took up comparable amounts of CO, over 24 h (see also Winter et al, 1992). Given this "compensatory" CO, uptake by day, curtailing nocturnal CAM activity had little effect on leaf photochemical efficiency in C. minor over the following day.…”
Section: Phases I1 and IVmentioning
confidence: 97%
“…This could represent futile cycling through malate production and decarboxylation , but a recent study on C. minor suggests that futile cycling is negligible during phase I1 in both control and N,-treated plants, although it may occur during phase IV (Borland and Griffiths, 1997; see also Osmond et al, 1996). In ,terms of overall carbon balance, regardless of the magnitude of phase I dark CO, uptake imposed by the various treatments, leaves took up comparable amounts of CO, over 24 h (see also Winter et al, 1992). Given this "compensatory" CO, uptake by day, curtailing nocturnal CAM activity had little effect on leaf photochemical efficiency in C. minor over the following day.…”
Section: Phases I1 and IVmentioning
confidence: 97%
“…soluble sugars form the major reserve carbohydrate pool, and both malic and citric acids may be accumulated at night (Popp et al, 1988;Borland et al, 1992;Franco et al, 1992). Moreover, it has recently been suggested that partitioning of fixed carbon between various biochemical fractions during the day controls the rapid switches between C3 and CAM in Clusia uvitana (Winter et al, 1992;Zotz and Winter, Plant Physiol. Vol.…”
Section: Minormentioning
confidence: 99%
“…Estimates of carbon-isotope discrimination expressed during CAM, derived from the trafficking among inorganic carbon, organic acids, and carbohydrate pools overnight, ranged from 0.9 to 3.1%0. The 613C of structural material did not change significantly between wet and dry seasons, indicating that most of the carbon used in growth was derived from C3 carboxylation.Clusia minor L. is a tropical dicotyledonous tree that shows extreme flexibility in regulating the relative amounts of C 0 2 fixed during the day and night in response to changes in the environment (Franco et al, 1990Borland et al, 1992Borland et al, , 1993Winter et al, 1992;Zotz and Winter, 1993). Under natural conditions, short-term changes in on-line, instantaneous A have illustrated how shifts in C3 and C4 carboxylation occur on a daily basis in C. minor, reflecting changes in environmental parameters (Borland et al, 1993).…”
mentioning
confidence: 99%
“…The genus harbours an exceptional diversity of life forms, which include terrestrial trees and shrubs, lianas, hemi-epiphytes and epiphytes (Zotz and Winter 1994a, b;Lüttge 1996). Clusia is singular in that not only do many species have the ability to grow as hemi-epiphytes, epiphytes or as terrestrial plants but the genus contains C 3 species and species that exhibit weak, inducible or obligate CAM (Franco et al 1990;Winter et al 1990Winter et al , 1992Borland et al 1992;Zotz and Winter 1993;Lüttge 1999), including the only known dicotyledonous CAM plants that exhibit a classic tree-like arborescent habit.…”
Section: Introductionmentioning
confidence: 99%